Hydrogen absorption behavior of non-stoichiometric Zr7-xTixV5Fe (x = 0, 0.3, 0.9, 1.5 and 2.1) alloys. (21st August 2020) - Han, Xingbo; Yan, Pan; Zhang, Dongxun; Lv, Lijun; Yang, Guo; Qin, Lailai; Leng, Haiyan; Liu, Wei
Abstract: Herein, the influence of Ti substitution on microstructure and hydrogen absorption behavior of annealed Zrx Ti7-x V5 Fe ( x  = 0, 0.3, 0.9, 1.5 and 2.1) alloys is systematically studied. The results reveal that the Ti-substituted alloys contain only α-Zr and C15–ZrV2 phases, where the content of C15–ZrV2 phase initially increased with increasing Ti content, followed by a gradual decrease. On the other hand, the content of α-Zr phase decreased with increasing Ti content, and then increased. Hence, the cell volume of C15–ZrV2 phase is maximum and the cell volume of α-Zr phase is minimum at x  = 1.5, corresponding to Zr5.5 Ti1.5 V5 Fe alloy. Moreover, the results exhibit that the plateau pressure of α-Zr phase increased with increasing Ti content at 623 K, 673 K and 723 K, whereas the plateau pressure of C15–ZrV2 phase exhibited the reverse change. Also, the stoichiometric ratio (A/B) of A-side element to B-side element in α-Zr phase gradually decreased with increasing Ti content, whereas the C15–ZrV2 phase exhibited an opposite trend. One should note that the A/B stoichiometric ratio may play a critical role in determining the plateau pressure of both phases. The hydrogen absorption curves of Zrx Ti7-x V5 Fe alloys showed that the hydrogen absorption content increased with increasing Ti content. It should be noted that the hydrogen absorption kinetics decreased with increasing Ti content, which may be mainly caused by increasing of the particle size with increasing Ti content. Highlights: The plateau pressure of C15 phase decreased with Ti substitution into Zr7 V5 Fe. The plateau pressure of α-Zr phase decreased with Ti substitution into Zr7 V5 Fe. The hydrogen absorption content of Zr7 V5 Fe increased with increasing Ti content. The substitution of Ti increased the pulverization resistance of Zr7 V5 Fe.